Clinical and genetic analysis of two wolfram syndrome families with high occurrence of wolfram syndrome and diabetes type II: a case report - Maryam Sobhani; Mohammad Amin Tabatabaiefar; Soudeh Ghafouri-Fard; Asadollah Rajab; Asal Hojjat; Abdol-Mohammad Kajbafzadeh; Mohammad Reza Noori-Daloii (BMC, 2020)
Abstract Background Mutations of the WFS1 gene are responsible for most cases of Wolfram syndrome (WS), a rare, recessively inherited neurodegenerative disorder characterized by juvenile-onset non-autoimmune diabetes mellitus and optic atrophy. Variants of WFS1 are also associated with non-syndromic hearing loss and type-2 diabetes mellitus (T2DM). Our study adds to literature significant associations between WS and T2DM. Case presentation In this study, we analyzed the clinical and genetic data of two families with high prevalence of WS and T2DM. Genetic linkage analysis and DNA sequencing were exploited to identify pathogenic variants. One novel pathogenic variant (c.2243-2244insC) and one known pathogenic (c.1232_1233delCT) (frameshift) variant were identified in exon eight of WFS1 gene. Conclusions The mutational and phenotypic spectrum of WS is broadened by our report of novel WFS1 mutation. Our results reveal the value of molecular analysis of WFS1 in the improvement of clinical diagnostics for WS. This study also confirms the role of WFS1 in T2DM.